Carnaval et patriotisme ou le paradoxe d’une festivité institutionnalisée rejetée - Dorothee Chouitem (Les Cahiers ALHIM)
During the last Uruguayan dictatorship (1973-1985), the defense of a nation’s existentialist vision and of the ideological borders became the main objective of the armed forces. In 1973, within the politics of consolidation of the national State, the Government set of an obligatory program of historic celebration entitled “1975: Año de la Orientalidad” with the aim of commemorate the one hundred fifty years of the 1825’s Cruzada Libertadora. This re-invention of the Uruguayan identity and of the social links, was passing by the reclamation of the criollo and rural Uruguay designated by the dictatorial regime as one of the depositories of the tradition and of the historic continuity. Carnival’s murgas as one of the older expression of an urban culture, were separated from the Orientalidad's ideological very restrictive conception. We analize in this contribution how paradoxically some murgas contributed to defend this ideological conception of the Orientalidad and, by the way, were singing the praises of the patriotism as defined by the armed forces.